Freshwater access in high salinity regions: impacts and adaptation insights from the Ganges River Delta - Yukyan Lam; Pamela J Surkan; Peter J Winch; Fosiul Alam Nizame (Inishmore Laser Scientific Publishing Ltd, 2018)
# Background Salinity, exacerbated by global environmental change and other phenomena, is a major challenge affecting densely populated river deltas around the world. One critical consequence of salinity is its effect on access to freshwater, crucial for drinking, hygiene, and other livelihood activities. To gain insight on the impacts and adaptation responses triggered by rising salinity, we conducted a multi-method study based in the Ganges river delta, in the region of southwest coastal Bangladesh. # Methods Data collection was conducted between May 2015 and January 2016. The study sites were three rural communities in the southwest coastal districts of Khulna, Satkhira, and Bagerhat. Across the sites, we conducted 83 in-depth interviews with community members and non-governmental organization (NGO) representatives and six community focus groups. Additionally, we surveyed water resources and management practices pertaining to 25 households, and measured the salinity of 45 surface and groundwater sources over two seasons. # Results Our results indicated a substantial and previously undocumented degree of seasonal and spatial variability in water salinity, a significant burden on inhabitants in accessing freshwater for consumption, and various health impacts from using saline water for hygiene purposes. Analysis of adaptation responses revealed that NGO efforts to provide household-level and community-level water options appeared unable to meet the demand. For household-level options, especially rainwater-harvesting tanks, unaffordability was a major problem. For community-level options, challenges consisted of poor upkeep of pond sand filter systems and non-compliance of rainwater-harvesting infrastructure sharing arrangements put in place by NGOs. New community-level adaptation strategies are under development, such as managed aquifer recharge systems and desalination plants, but similar challenges are projected. # Conclusions Our findings suggest firstly the inadequacy of existing metrics for capturing water insecurity in our changing environment. Secondly, additional research on the social and economic aspects of adaptation responses is as necessary as study of their technical attributes. Household-level interventions, considered less 'cost-effective' by development actors, may still be important for ensuring universal access to freshwater. These findings lay the groundwork for the design of future quantitative studies and adaptation initiatives in the Ganges delta, as well as other salinity-affected, low-resource deltaic regions.